Peran Mudir dalam Menanamkan Moderasi Beragama Demi Mencegah Tindak Terorisme di Lingkungan Pesantren Mustahafawiyah Mandailing Natal - Arianto, Nanang; Datuk Imam Marzuki; Susanti Hasibuan; Desiana (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2024)
Mudir is actually the highest leader in the Islamic boarding school and is an icon of the Islamic boarding school itself. The mudir must be at the forefront and be the spearhead of the Islamic boarding school's progress. Mudir must also play a role in preventing the flow of radicalism from spreading within the Musthafawiyah Islamic boarding school. And currently H. Mustafa Bakri Nasution is believed to be the mudir of the Musthafawiyah Islamic boarding school who has a very important role in maintaining the ideological traditions of the Musthafawiyah Islamic boarding school. The aim of this research is to see the role of H. Mustafa Bakri Nasution as the mudir of the Musthafawiyah Islamic boarding school in preventing radicalism from targeting its students, and how the mudir's efforts to implement the ideology of religious moderation within the Musthafawiyah Islamic boarding school environment. The purpose of this study is to see how the role of H. Mustafa Bakri Nasution as the head of the Musthafawiyah Islamic boarding school in preventing radicalism that targets his students, and how the head's efforts to implement religious moderation in the Musthafawiyah Islamic boarding school environment. This study uses a qualitative methodology by making students, educators and the head as data collection instruments and using descriptive as a technique for describing it. The results of this study indicate that the role of the head of the Musthafawiyah Islamic boarding school in preventing the entry of radicalism is by controlling the curriculum to comply with the Ministry of Education and Technology and controlling the quality of ustadz/ustadzah as educators at the Islamic boarding school. In addition, the head is selective about thoughts that come from outside, and collaborates with parties who contribute to bringing Islamic thought that develops in accordance with Islamic teachings that have become a traditional ideology in the Mustafawiyah Islamic boarding school environment.